2014
DOI: 10.1002/hep.26965
|View full text |Cite
|
Sign up to set email alerts
|

Vascular cell adhesion molecule 1 expression by biliary epithelium promotes persistence of inflammation by inhibiting effector T-cell apoptosis

Abstract: Chronic hepatitis occurs when effector lymphocytes are recruited to the liver from blood and retained in tissue to interact with target cells, such as hepatocytes or bile ducts (BDs). Vascular cell adhesion molecule 1 (VCAM‐1; CD106), a member of the immunoglobulin superfamily, supports leukocyte adhesion by binding α4β1 integrins and is critical for the recruitment of monocytes and lymphocytes during inflammation. We detected VCAM‐1 on cholangiocytes in chronic liver disease (CLD) and hypothesized that biliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…This is consistent with other studies showing an increase in VCAM-1 expression associated with chronic liver and biliary diseases 73 . As observed in this study, VCAM-1 expression is low in resting, undamaged cells but during liver inflammation its expression increases, and is believed to be important for recruitment of monocytes and lymphocytes 7476 .…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with other studies showing an increase in VCAM-1 expression associated with chronic liver and biliary diseases 73 . As observed in this study, VCAM-1 expression is low in resting, undamaged cells but during liver inflammation its expression increases, and is believed to be important for recruitment of monocytes and lymphocytes 7476 .…”
Section: Discussionsupporting
confidence: 94%
“…26,27 More recently, Wang et al 28 reported that the up-regulation of IL-17 production in CD4 + T cells in chronic hepatitis C patients, and elevated Tim-3 signalling on CD14 + monocytes impaired the balance of IL-12/IL-23 through the intracellular signal transducer and activator of transcription 3 signalling, which led to the IL-17 secretion and Th17 cell development. Afford et al 29 also confirmed that vascular cell adhesion molecule 1 (VCAM-1) promotes liver inflammation by inducing lymphocyte recruitment and Th17 cell survival. Those studies revealed the association between Th17 cells and liver inflammation.…”
Section: Discussionmentioning
confidence: 94%
“…IL-2 receptor α gene deficiency in mice causes biliary inflammation resembling PSC[40]. Integrin ligands, intracellular adhesions molecule 1, and vascular cell adhesion molecule 1 are also expressed by the biliary epithelium and contribute to the recruitment of inflammatory leukocytes that play a role in development of biliary inflammation seen in PSC[41]. Gut-specific T and B cells can be programmed to perpetuate biliary inflammation after encountering an enteric pathogen, providing an important rationale of how liver and gut inflammation may be linked[42].…”
Section: Pathogenesismentioning
confidence: 99%